1998
DOI: 10.1093/humrep/13.9.2421
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic intravenous hydroxyethyle starch solution prevents moderate-severe ovarian hyperstimulation in in-vitro fertilization patients: a prospective, randomized, double-blind and placebo- controlled study

Abstract: A prospective, randomized, double-blind and placebo-controlled study was conducted to assess the effectiveness of i.v. administration of 6% hydroxyethyle starch solution (HES) in preventing moderate and severe ovarian hyperstimulation syndrome (OHSS) in patients in an in-vitro fertilization programme. A total of 101 women who had serum oestradiol concentrations >1500 pg/ml and/or more than 10 follicles on day of human chorionic gonadotrophin (HCG) administration were recruited into two groups: HES group (n = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…In that report, no significant difference was observed in the incidence of severe OHSS between the treatment group and a historical control group, although the incidence of moderate OHSS was reduced. A subsequent RCT assessed the effectiveness of 1,000 ml of 6% HES administered at the time of embryo transfer in women thought to be at high risk of OHSS [25] . The incidence of moderate/severe OHSS was significantly lower in the treatment group compared with the placebo group [2% (1/51) vs. 13% (7/53)].…”
Section: Discussionmentioning
confidence: 99%
“…In that report, no significant difference was observed in the incidence of severe OHSS between the treatment group and a historical control group, although the incidence of moderate OHSS was reduced. A subsequent RCT assessed the effectiveness of 1,000 ml of 6% HES administered at the time of embryo transfer in women thought to be at high risk of OHSS [25] . The incidence of moderate/severe OHSS was significantly lower in the treatment group compared with the placebo group [2% (1/51) vs. 13% (7/53)].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to albumin namely hydroxyethyle starch solution (HES), a plasma colloid substitute has been tested in a prospective, randomised, double-blind placebo-controlled study [38] and showed a significant benefit in the treatment group ( p = 0.031). …”
Section: Albuminmentioning
confidence: 99%
“…13 Finally, HES 200/0.5 was as effective as albumin in the prevention of ovarian hyperstimulation syndrome, a condition also characterized by arterial vasodilation, marked decrease in arterial blood volume, and ascites. [14][15][16] Von Willebrand factor is synthesized by endothelial cells and released in response to mechanisms that also stimulate NO release, such as cytokines and shear stress. It is considered to be a marker of endothelial activation.…”
mentioning
confidence: 99%